Attitudes towards Bachelor-level education amongst Bavarian midwives: Results of a descriptive cross-sectional survey in Bavaria, Germany - Reuschenbach, Bernd (Eur J Midwifery, 2018)
INTRODUCTION: In Germany, the traditional vocational midwifery training lasts three years. This training is marked as Qualification Level 4 of the European Qualification Framework (EQF). There are very few midwives with a Bachelor degree, and an even smaller number of universities that offer a qualification program at EQF Level 6 (Bachelor). The aim of this paper is to analyze the attitude and interests of traditionally educated German midwives in undertaking a university degree. METHODS: Midwives were surveyed within the framework of a descriptive cross-sectional study. The survey has 13 items and was available as a web-based survey between 1 November 2016 and 31 January 2017. Alternatively, the midwives were able to send a hardcopy version of the questionnaire back by mail, anonymously. Data was obtained from 534 midwives. The quantitative data were analyzed using SPSS (Version 23). The qualitative data were structurally analyzed using a qualitative content analysis. RESULTS: It was found that 57.7% of the surveyed midwives are interested in completing a university degree, and 40.1% could imagine themselves pursuing a degree. The respondents were overwhelmingly positive in their opinion of university qualifications and qualification upgrades. Nevertheless, the open-question responses indicated that there are strong concerns surrounding the level of proficiency and experience-based knowledge taught for a university degree, which are essential elements in the traditional training system. CONCLUSIONS: Although midwives understand the importance of a Bachelor degree, they need to be informed about the expertise and practical skills taught in the degree curriculum.